Análisis de contenidos en radio Universidad de Bolívar 102.3 FM y su contribución a la difusión de la cultura Waranka, en la comunidad Vinchoa, cantón Guaranda período mayo - noviembre 2023 - Moreira Rodriguez, Dennis Arturo (2024)
This research aims to analyze how the programming of the University of Bolívar 102.3FM radio contributes to the dissemination of Waranka culture in the Vinchoa community, Guaranda canton, during the period May November 2023, to identify improvements that strengthen the preservation and promotion of this cultural identity and is carried out taking into account the theoretical, exploratory and descriptive scope of research; the hypothetical deductive, analytical and probabilistic methods, which are carried out with the help of techniques and instruments, data collection that includes observation, interview conducted with the director of Radio Universidad de Bolívar 102.3 FM and a sociologist, in addition, the survey applied to a sample of 180 inhabitants of the La Vinchoa community that resulted in the absence of specific programs regarding Waranka culture but the existence of a space called Cultural Waranka where generalized topics are addressed that allow us to learn about native music. festivities and works that are carried out, therefore, this information does not generate interest to the members of this town and 50% rarely consume the content provided by this means of communication, additionally it takes place in the afternoon when the community members are together. In their work, therefore, it is advisable to update the programming grid and establish a cultural space, as well as involve the community through interviews and opinions regarding the traditional experiences and other aspects of the Waranka.